Delayed rectifying and calcium-activated K+ channels and their significance for action potential repolarization in mouse pancreatic beta-cells. - Smith, P; Bokvist, K; Arkhammar, P; Berggren, P; Rorsman, P (1990)
The contribution of Ca2(+)-activated and delayed rectifying K+ channels to the voltage-dependent outward current involved in spike repolarization in mouse pancreatic beta-cells (Rorsman, P., and G. Trube. 1986. J. Physiol. 374:531-550) was assessed using patch-clamp techniques. A Ca2(+)-dependent component could be identified by its rapid inactivation and sensitivity to the Ca2+ channel blocker Cd2+. This current showed the same voltage dependence as the voltage-activated (Cd2(+)-sensitive) Ca2+ current and contributed 10-20% to the total beta-cell delayed outward current. The single-channel events underlying the Ca2(+)-activated component were investigated in cell-attached patches. Increase of [Ca2+]i invariably induced a dramatic increase in the open state probability of a Ca2(+)-activated K+ channel. This channel had a single-channel conductance of 70 pS [( K+]o = 5.6 mM). The Ca2(+)-independent outward current (constituting greater than 80% of the total) reflected the activation of an 8 pS [( K+]o = 5.6 mM; [K+]i = 155 mM) K+ channel. This channel was the only type observed to be associated with action potentials in cell-attached patches. It is suggested that in mouse beta-cells spike repolarization results mainly from the opening of the 8-pS delayed rectifying K+ channel.